Charge State Control of F16CoPc on h‐BN/Cu(111). Issue 15 (3rd June 2020) - Pörtner, Mathias; Wei, Yinying; Riss, Alexander; Seufert, Knud; Garnica, Manuela; Barth, Johannes V.; Seitsonen, Ari P.; Diekhöner, Lars; Auwärter, Willi
Abstract: The use of molecular materials in solar cells and nano‐electronics demands a fundamental understanding and control of their electronic properties. Particularly relevant is the molecular response to the environment, that is, the interaction with the support and adjacent molecules, as well as the influence of electrostatic gating. Here, the control of molecular level alignment and charge states of fluorinated cobalt phthalocyanines (F16 CoPc) on atomically thin hexagonal boron nitride ( h ‐BN) sheets on Cu(111) is reported using scanning tunneling microscopy (STM) and spectroscopy (STS), as well as atomic force microscopy (AFM) and complementary density functional theory (DFT) calculations. Three parameters that govern the electronic level alignment of F16 CoPc orbitals are investigated: i) template‐induced gating by the work function variation of the h ‐BN/Cu(111) substrate, ii) gating by the STM tip, and iii) screening by neighboring molecules. The interplay of these parameters influences the charge distribution in the studied molecular arrangements and thus provides the possibility to tune their physicochemical behavior, for instance, the response toward electronic or optical excitation, charge transport, or binding of axial adducts. Abstract : The control of molecular properties at interfaces is crucial for the design and functionality of molecular electronic devices and hybrid materials. This work demonstrates how molecular orbitals and charge states can be modified by gating and screening. Specifically, phthalocyanines adsorbed on a super‐structured hexagonal boron nitride monolayer are addressed and controlled on the single molecule level, using scanning probe microscopy.